Religious Insight: Ethnozoology of Tota’an Dove Jember - Jamil, Robit Nurul (el Harakah: Jurnal Budaya Islam, 2023)
In Jember's culture, dove symbolizes peace and purity. Tota'an tradition captures attention as a cultural symbol that fosters a sense of brotherhood, connecting communities. This study delves into the role of local culture in strengthening interpersonal relationships, transcending beyond cultural expressions. Using ethnozoology, it explores the perspectives and roles of doves in the Tota'an tradition. The research focuses on examining the Tota'an tradition in three lenses: ethnozoology, local culture, and Islam. It seeks to understand how Islamic values, such as solidarity and compassion, are reflected in Tota'an, and how these values are connected to ethnozoological aspects, particularly the symbolism of doves. The result presents the exploration of the analysis of Tota'an's impact in the Islamic context. It emphasizes the intricate balance formed by local culture, serving as a bridge between Islam and ethnozoology. It also provides profound insights into the interconnected relationship of ethnozoology, local culture, and Islam through Tota'an. By following a specific sequence in examining the tradition, it reveals deeper layers of meaning, enhancing our understanding of the mutual reinforcement of values within the context of the vibrant local culture. By preserving and understanding the cultural and religious values in Tota'an, the Jember community can maintain their cultural identity while strengthening social cohesion. Dalam budaya Jember, merpati dianggap sebagai simbol perdamaian dan kesucian. Tradisi Tota’an, menarik perhatian masyarakat, sebagai simbol budaya yang menghubungkan masyarakat dalam semangat persaudaraan, sehingga tradisi ini perlu dilestarikan. Penelitian ini menggali peran budaya lokal dalam memperkuat hubungan interpersonal, melampaui sekadar ekspresi budaya semata. Dengan menggunakan etnozoologi, penelitian ini menjelajahi perspektif dari merpati sebagai tradisi Tota'an. Penelitian ini fokus menguji tradisi Tota'an melalui tiga lensa: etnozoologi, budaya lokal, dan Islam. Tujuannya memahami bagaimana nilai-nilai Islam, seperti solidaritas dan welas asih, tercermin dalam tradisi Tota'an, dan bagaimana nilai-nilai tersebut terhubung dengan aspek etnozoologi, khususnya simbolisme merpati. Hasil penelitian menyajikan pemaparan analisis dampak Tota'an dalam konteks Islam. Studi ini menekankan keseimbangan kompleks yang terbentuk oleh budaya lokal, berfungsi sebagai jembatan antara Islam dan etnozoologi. Penelitian ini memberikan wawasan mendalam tentang hubungan terkait etnozoologi, budaya lokal, dan Islam melalui tradisi Tota'an. Dengan mengikuti urutan spesifik dalam mengkaji tradisi, penelitian ini mengungkap lapisan makna yang lebih dalam, meningkatkan pemahaman tentang penguatan nilai-nilai yang saling berhubungan dalam konteks budaya lokal yang dinamis. Dengan melestarikan dan memahami nilai-nilai budaya dan agama dalam Tota'an, masyarakat Jember dapat menjaga identitas budaya mereka serta memperkuat koherensi sosial.